Extinção antecipada das concessões de serviços públicos: um estudo sobre a encampação - Silva, José Victor Pallis da (2025)
This dissertation focuses on the investigation of one of the modalities of early termination of public service concessions, which occurs through a unilateral act of the Public Authority, called “encampação”. According to Article 37 of Law No. 8,987, dated February 13, 1995, this act (i) shall be based in “reasons of public interest,” (ii) must be preceded by a “specific authorizing law,” and (iii) shall only be effective after the payment of “prior compensation” to the concessionaire. The study is based on the hypothesis that the voluntary termination by the Authority should be investigated in light of the contractual dimension of public service concessions, which allows elucidation of both the foundations of this institute and the legal contours brought by Law No. 8,987/1995. Through legislative, bibliographic, and jurisprudential analysis, the study presents (i) the preliminary contours of the institute, (ii) the historical investigation of its use in Brazilian administrative practice, and (iii) the analysis of the main rulings of Brazilian courts on the subject. Subsequently, the constitutional and legal contours of the encampação are presented, with emphasis on the relevant constitutional principles and a detailed analysis of each of the three requirements brought by Article 37 of Law No. 8,987/1995. Finally, the study seeks to map the possibilities and limits of judicial control over the administrative act that decrees the voluntary termination of the concession contract by the Public Authority, both by the Judiciary and by potential arbitral tribunals